2016
DOI: 10.1177/0003489415625075
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Autologous Fascia Implantation With Controlled Release of Fibroblast Growth Factor for Recurrent Laryngeal Nerve Paralysis Due to Long-term Denervation

Abstract: The ATFV with controlled release of bFGF repaired the glottal gap and laryngeal volume after RLN section and may reduce the occurrence of aspiration and hoarseness. We speculate that this treatment improves laryngeal function in long-term RLN denervation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“… 35 However, another report has suggested that an inappropriate dose of bFGF produces granulation tissue. 30 Komura et al reported the effectiveness of intra-tracheal injection with a concentration of 200 μg/mL bFGF for tracheal cartilage growth, and no changes in breathing condition or formation of granulation tissue on histological examination were observed in any of the rabbits in their study. 36 Because the trachea and larynx are continuous structures that form the airway, we determined a concentration of 200 μg/mL bFGF to be a safe concentration for intra-laryngeal injection for the prevention of suffocation caused by bFGF side effects.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“… 35 However, another report has suggested that an inappropriate dose of bFGF produces granulation tissue. 30 Komura et al reported the effectiveness of intra-tracheal injection with a concentration of 200 μg/mL bFGF for tracheal cartilage growth, and no changes in breathing condition or formation of granulation tissue on histological examination were observed in any of the rabbits in their study. 36 Because the trachea and larynx are continuous structures that form the airway, we determined a concentration of 200 μg/mL bFGF to be a safe concentration for intra-laryngeal injection for the prevention of suffocation caused by bFGF side effects.…”
Section: Discussionmentioning
confidence: 84%
“…A number of studies have addressed the effectiveness of a combination of biodegradable gelatin hydrogel with controlled release of bFGF for the regeneration of damaged tissues or organs, including the skull bone, 26 limbs, 27 facial nerves, 28 tympanic membrane 29 and laryngeal nerves. 30 No side effects due to the biodegradable gelatin hydrogel with bFGF have been observed in several previous studies, such as those focused on bone defects in rabbits, 26 streptozotocin-induced diabetes in rats 31 and skin ulcers in mice. 32 There have been no reports on the use of injecting biodegradable gelatin hydrogel microspheres with bFGF into vocal folds immediately after surgical procedures.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, Nagai et al 25 14 These improvements were observed in both female (with small larynxes) and male patients (with larger larynxes). 14 Thus, previous results have demonstrated the short-term efficacy and safety of vocal fold bFGF injection therapy.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Goto et al 24 reported that in rats with recurrent laryngeal nerve paralysis, a single injection of bFGF augmented the regeneration and differentiation of atrophic thyroarytenoid muscles by enhancing the proliferation and differentiation of muscle satellite cells. In addition, Nagai et al 25 conducted fascial transplantation experiments in rats with a severed recurrent nerve and demonstrated that bFGF significantly reduced the glottic gap and increased the volume of residual fascia and fat in the paralyzed vocal folds. Tamura et al 26 demonstrated that bFGF injection in the vocal fold helped maintain the adipose tissue in the paralyzed vocal cords of experimental beagle dogs.…”
Section: Discussionmentioning
confidence: 99%
“…10 Implantation of autologous fascia as a scaffold is thus suitable because host cells can easily infiltrate the scaffold and are influenced by bFGF. 30 Our previous study 31 showed that the implantation of autologous fascia with or without the controlled release of bFGF could increase the volume of the atrophic lateral TA muscle, thereby diminishing the glottal gap after RLN paralysis. Phonations contribute not only to the glottal position but also to the lung function and oral-pharyngeal condition.…”
Section: Discussionmentioning
confidence: 99%